Diagnóstico de leucemia e inmunodeficiencia felina a través de inmunocromatografía en gatos atendidos en las clínicas veterinarias de la ciudad de Loja - Ordoñez Jadan, Angie Iharen (2024)
Feline leukemia virus (FeLV) and feline immunodeficiency virus (FIV) are among the most common infectious agents in cats, causing immunosuppression, increasing susceptibility to the presence of other opportunistic agents that develop serious secondary diseases, most of them fatal. The aim of this research was to identify the presence of FeLV antigen and FIV antibodies using the immunochromatographic method (SensPERT FeLV Ag/FIV Ab), to evaluate the values of the hemogram, and to relate variables such as sex, age, reproductive status, access to the outdoors and coexistence with other cats to the presence of the diseases. Sixty-three patients who came for consultation to the clinics “Emergencias Veterinarias” and “Animal Center” in the city of Loja participated, reporting 39.7% positive for the presence of FeLV and 3.2% positive for the presence of FIV. Through the parametric Student's T method and the non- parametric Wilcoxon test, the analytes were compared between positive and negative cases; to determine the variables associated with the diseases, Fisher's exact test was applied. In the analysis of the hemogram of FeLV there was a decrease (p= 0.001) in erythrocytes, hemoglobin and hematocrit in positive patients with low platelets in relation to the reference range. In the case of FIV there was evidence of a decrease (p= 0.005) in monocytes in positive cases. The variable access to the exterior was the only factor associated with the presence of FeLV (p= 0.021) with the highest percentage in the item cats of mixed stay with 56.3%; for FIV there is no association with the presence of the disease. In the city of Loja, there is a greater identification of cats with the presence of FeLV antigen, showing a decrease in the red line and platelets, whose influential factor to its presence is the access to the exterior.